TINJAUAN PAKAIAN ADAT BUNDO KANDUANG DI KENAGARIAN KOTO TINGGI KECAMATAN BASO KABUPATEN AGAM SUMATERA BARAT - RELA GUSPARINI, Dra. Zubaidah,M.Sn, Dra. Zubaidah, M.Pd (Serupa The Journal of Art Education, 2014)
The purpose of this study is to describe the type, device form, function and meaning in traditional clothes Bundo Kanduang Kenagarian Koto Tinggi subdistrict Baso. The data source of this research is from the informen. Data collected using the method of observation, interview and documentation. The study's findings that there are five types of custom clothing Bundo Kanduang in Kenagari Koto Tinggi. Each type pakian masiang The device has four principal forms, namely: tangkuluak (headgear), baju kurung (clothes), kodek (sheath) and sandang (shawl). Each type has a different function. The form of custom clothing Bundo Kanduang have relevance to the role Bundo Kanduang itself.Kata Kunci : Pakaian Adat